Research and apply of the quality of star image for star tracker - SHEN Yuteng, ZHANG Chi (Zhihui kongzhi yu fangzhen, 2025)
In recent years,with the development of commercial spaceflight, the requirements of the production quality for star tracker in commercial satellite become higher and higher. In this paper,“Seven Parameter Image Quantitative Evaluation Standard”is developed, which makes use of the massive star image data accumulated in the production of star tracker and through data modeling theory research. The adjustment of optical machine for Pi star tracker use this standard, and the final measurement accuracy of the product for Pi star tracker was verified by stargazing test, which prove the standard is effectively and can improve the consistency of measurement accuracy of the product for Pi star tracker.